Current Strategies and Future Directions to Optimize ACL Reconstruction in Adolescent Patients - Richter, Dustin Jon; Lyon, Roger; Van Valin, Scott; Liu, Xue-Cheng (Frontiers in Surgery, 2018)
The incidence of anterior cruciate ligament (ACL) injuries in the pediatric population has risen in recent years. These injuries have historically presented a management dilemma in skeletally immature patients with open physes and significant growth remaining at time of injury. While those nearing skeletal maturity may be treated with traditional, transphyseal adult techniques, these same procedures risk iatrogenic damage to the growth plates and resultant growth disturbances in younger patients with open physes. Moreover, conservative management is non-optimal as significant instabilities of the knee remain. Despite the development of physeal-sparing reconstructive techniques for younger patients, there remains debate over which procedure may be most suitable on a patient to patient basis. Meanwhile, the drivers behind clinical and functional outcomes following ACL reconstruction remain poorly understood. Therefore, current strategies are not yet capable of optimizing surgical ACL reconstruction on an individualized basis with absolute confidence. Instead, aims to improve surgical treatment of ACL tears in skeletally immature patients will rely on additional approaches in the near future. Namely, finite element models have emerged as a tool to model complex knee joint biomechanics. The inclusion of several individualized variables such as bone age, three dimensional geometries around the knee joint, tunnel positioning, and graft tension collectively present a possible means of better understanding and even predicting how to enhance surgical decision-making. Such a tool would serve surgeons in optimizing ACL reconstruction in the skeletally immature individuals, in order to improve clinical outcomes as well as reduce the rate of post-operative complications.